THE EFFECT OF LEARNING STRATEGY AND MOTIVATION AT THE LEARNING OUTCOMES FOR PHYSICAL EDUCATION, SPORTS AND HEALTH IN ELEMENTARY SCHOOLS - Irfan; Sudirman Burhanuddin; Ihsan Abbas (EDU RESEARCH, 2023)
The study aims to determine the effect of learning strategy and motivation at the leaning outcomes for physical education, sports and health in elementary schools. This is a kind of experimental research by factorial design. The sample used was 40 students at SD Inpres Tallang-Tallang. Data analysis technique used is descriptive statistical analisys and 2 ways Anova. Hypothetical test results show: (1) The are differences in learning outcomes between students who follow the discovery leanirng strategy which is higher tha the expository strategies in physical education subjects in elementary schools. (2) The are interactions between learning strategies with motivation at the learning outcomes in physical education subjects in elementary schools. (3) The are differences in learning outcomes between students through discovery leanirng strategy which is higher tha the expository strategies which have high motivation in physical education subjects in elementary schools. (4) The are differences in learning outcomes between students through discovery leanirng strategy which is higher tha the expository strategies which have low motivation in physical education subjects in elementary schools.